2020
DOI: 10.1101/2020.08.07.20169490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV infection and COVID-19 death: population-based cohort analysis of UK primary care data and linked national death registrations within the OpenSAFELY platform

Abstract: Background: It is unclear whether HIV infection is associated with risk of COVID-19 death. We aimed to investigate this in a large-scale population-based study in England. Methods: Working on behalf of NHS England, we used the OpenSAFELY platform to analyse routinely collected electronic primary care data linked to national death registrations. People with a primary care record for HIV infection were compared to people without HIV. COVID-19 death was defined by ICD-10 codes U07.1 or U07.2 anywhere on the dea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
153
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(173 citation statements)
references
References 19 publications
16
153
2
2
Order By: Relevance
“…However, a recent meta‐analysis has reported an increased pooled prevalence of HIV in COVID‐19 patients (1.22%, 95% CI, 0.61%–2.43%) in comparison to the general population of (0.65%; 95% CI, 0.48%–0.89%). Another population‐based cohort study from the UK have reported PLHIV had a higher risk of COVID‐19 death than those without HIV (HR = 2.90; 95% CI, 1.96–4.30) 55 . PLHIV should not be considered as protected from SARS‐CoV‐2 as people with low CD4 cell counts may have poorer outcomes than people with normal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta‐analysis has reported an increased pooled prevalence of HIV in COVID‐19 patients (1.22%, 95% CI, 0.61%–2.43%) in comparison to the general population of (0.65%; 95% CI, 0.48%–0.89%). Another population‐based cohort study from the UK have reported PLHIV had a higher risk of COVID‐19 death than those without HIV (HR = 2.90; 95% CI, 1.96–4.30) 55 . PLHIV should not be considered as protected from SARS‐CoV‐2 as people with low CD4 cell counts may have poorer outcomes than people with normal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears that well-controlled HIV individuals are not at greater of severe COVID-19 respect poorly controlled HIV individuals, which may have worse outcomes. In a large population-based study in the UK (from the Open SAFELY platform), it has been reported that individuals with HIV have more than twice the probability of dying from COVID-19 than people without HIV [ 136 ]. This conclusion was reached after adjustment for a range of potential confounders such as demographic characteristics, the factors related to the personal lifestyle, and considering any comorbidities.…”
Section: Interrelation Between Covid-19 and Disorders With Mixed Or Mmentioning
confidence: 99%
“…In The Lancet HIV, Khrishnan Bhaskaran and colleagues 2 have analysed COVID-19 deaths in people with HIV from OpenSAFELY, a UK primary care database of 17·3 million adults. Mortality among the 27 480 people with HIV (0·16% of the study population) was higher than the general population with an adjusted hazard ratio of 2·59 (95% CI 1·74–3·84; p<0·0001).…”
mentioning
confidence: 99%